Preparation method of fuel electrode, fuel electrode, fuel cell and electrolytic tank
Patent Information
- Application Number
- CN202411253918.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-06
AI Technical Summary
In the prior art, the microstructure regulation of fuel electrodes is limited by the carrier structure, and the pore size range regulated by the pore maker is limited, so it cannot be precisely regulated, which affects electrochemical performance.
The fuel electrode with gradient pore structure is prepared by solid phase synthesis method. By controlling the particle size and mass ratio of nickel oxide and gadolinium doped cerium oxide, combined with the ball milling and calcining process, the porosity and pore size are accurately controlled to form a stacked pore structure, and the stacked pore structure is improved. Electrochemical reaction rate and stability.
Accurate control of the extremely microstructure of the fuel is achieved, electrochemical performance and stability is improved, and core renewable fuel devices such as carbon monoxide that are suitable for high-temperature electrolysis of water and carbon monoxide to prepare hydrogen.
Smart Images

Figure CN119133474A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid oxide fuel cells or electrolytic cells, and in particular to a method for preparing a fuel electrode, a fuel electrode, a solid oxide fuel cell and a solid oxide fuel electrolytic cell. Background Art
[0003] Solid oxide fuel cell (SOFC) is a power generation device that directly converts the chemical energy of fuel into electrical energy. It is not limited by the Carnot cycle and therefore has higher efficiency. Solid oxide electrolytic cell (SOEC) can be regarded as the reverse mode of SOFC. Its high temperature working conditions can overcome the disadvantage of limited electrolytic reaction activity at low temperatures and achieve efficient electrolysis of water and carbon dioxide to produce hydrogen, carbon monoxide and other renewable fuels. The cycle of hydrogen production and power generation based on SOFC / SOEC (hereinafter collectively referred to as Solid oxide cell, SOC) technology can not only achieve the purpose of energy storage, but also realize the resource reduction of carbon dioxide emissions, which is of great significance to solving the energy crisis and global warming.
[0004] According to the type of support used, SOC can be divided into three types: electrolyte-supported, electrode-supported, and metal-based. Electrode-supported SOC uses a thinner electrolyte with lower ohmic impedance, but the electrode thickness needs to be significantly increased to meet the mechanical strength requirements of SOC, making the mass transfer process, the polarization process of the supporting electrode, the physical and chemical properties of the supporting electrode, and the microstructural changes become the main factors limiting performance. The thickness of the electrolyte and electrode of the metal-supported SOC is relatively thin, which effectively solves the problems of electrolyte ohmic impedance and electrode polarization impedance while taking into account the mechanical strength and mechanical properties of the SOC. However, the metal support also causes some negative effects, which not only increases the complexity of the SOC preparation process, limits the selectivity of the connector material, but also limits the high-temperature working ability of the metal-supported SOC (<600°C). Therefore, the inherent structural stability and high-temperature tolerance of the electrolyte-supported SOC make it more suitable for the needs of core devices for renewable fuels such as high-temperature electrolysis of water, preparation of hydrogen from carbon dioxide, and carbon monoxide. The electrolyte thickness of the electrolyte-supported SOC is relatively thick and has a higher ohmic impedance. The optimization of electrode function is the key issue in realizing high-temperature electrolysis with the electrolyte-supported SOC as the core component. The fuel-side electrode (hereinafter referred to as the fuel electrode) is the main area where the redox reaction of the fuel occurs, and therefore has a crucial impact on the performance of the SOC.
[0005] In the preparation of the fuel electrode, the particle size and other physical and chemical properties of the mixture powder of metal oxide and oxygen ion conductor, the ratio of powder to binder, additives, especially pore-forming agents have an important influence on the microstructure, mass transfer process and electrochemical reaction process of the fuel electrode. Reasonable regulation of the above important parameters is of great significance to improving the performance of the fuel electrode of electrolyte-supported SOC. Among them, the mainstream fuel electrode used in large-scale electrolyte-supported SOC is a composite film of a mixture of metal oxide and oxygen ion conductor, such as nickel oxide / gadolinium doped cerium oxide (NiO / CGO). The melting point of metal nickel (Ni) can reach 1453°C, so it is widely used to prepare fuel electrodes under high temperature working conditions, and nickel oxide / gadolinium doped cerium oxide (NiO / CGO) has high electron transport performance, ion transport performance and electrocatalytic activity.
[0006] In the prior art, for example: the patent application number is CN202211684484.7, and the invention name is solid oxide fuel cell anode and its preparation method, single cell and stack; the patent discloses a solid oxide fuel cell anode, which includes nickel foam and YSZ / NiO porous ceramics loaded on nickel foam. By using nickel foam as a carrier, taking advantage of its natural large number of pores, good ductility and easy cutting into various shapes, NiYSZ composite slurry is loaded on nickel foam to prepare SOFC anode, so that the anode naturally has a large number of pores, good ductility, and a formed Ni network, so that the SOFC anode has good mechanical properties and good electronic conductivity, which can meet different usage needs.
[0007] Ye Fei. Preparation and characterization of gradient cathode materials for solid oxide fuel cells [D]. Zhejiang University, 2008; The literature uses spin coating to prepare cathode thin layers with functional gradient structures by changing the content of components, viscosity agents and pore-forming agents in the slurry. The design of multi-layer functional gradient structure cathode thin layers solves the problem of rapid increase in battery cathode polarization resistance at medium and low temperatures.
[0008] As can be seen from the above, the prior art regulates the microstructure of the fuel electrode by means of a carrier. However, the method of relying on the carrier makes the microstructure of the fuel electrode depend on the structure of the carrier, and thus the range of adjustable microstructures is very limited. Or the microstructure of the fuel electrode is mainly regulated by using a pore former. The working principle of the pore former is that the pore former volatilizes into a gas at a certain temperature, overflows from the material, and thus the material has a porous structure. However, the range of pore sizes regulated by the pore former is limited and cannot be precisely regulated. Based on this, it is expected that the microstructure of the fuel electrode can be regulated without using a pore former or a carrier, and a fuel electrode with better electrochemical performance can be prepared. Summary of the invention
[0009] In order to solve the above technical problems, the present invention provides a fuel electrode and a preparation method thereof.
[0010] In a first aspect, an embodiment of the present invention discloses a method for preparing a fuel electrode, comprising the following steps:
[0011] Preparation of adhesion layer precursor: Gadolinium-doped cerium oxide (CGO) is first calcined to obtain an adhesion layer precursor, and the temperature of the first calcination is 1000-1100° C.;
[0012] Preparation of adhesive layer suspension slurry: mixing an adhesive layer precursor and a binder to form an adhesive layer suspension slurry;
[0013] Preparation of functional layer precursor: After ball milling and mixing nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO), a second calcination is performed to obtain a functional layer precursor, wherein the particle size of the selected nickel oxide (NiO) is 1-2 μm, the particle size of the gadolinium-doped cerium oxide (CGO) is 300-500 nm, the mass ratio of nickel oxide (NiO) to gadolinium-doped cerium oxide (CGO) is 1-2:1, and the temperature of the second calcination is 1000-1100° C.;
[0014] Functional layer suspension slurry preparation: functional layer precursor, binder and dispersant are mixed to form functional layer suspension slurry;
[0015] Preparation of a collector layer precursor: After ball milling and mixing nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO), the third calcination is performed to obtain a collector layer precursor, wherein the particle size of the selected nickel oxide (NiO) is 4-5 μm, the particle size of the gadolinium-doped cerium oxide (CGO) is 300-500 nm, the mass ratio of nickel oxide (NiO) to gadolinium-doped cerium oxide (CGO) is 3-5:1, and the temperature of the third calcination is 1000-1100° C.;
[0016] Preparation of collector layer suspension slurry: mixing collector layer precursor, binder and dispersant to form collector layer suspension slurry;
[0017] Preparation of fuel electrode embryo: coating the adhesion layer suspension slurry, the functional layer suspension slurry and the collector layer suspension slurry on the electrolyte surface in sequence to obtain a fuel electrode embryo with a three-layer structure of adhesion layer, functional layer and collector layer;
[0018] Preparation of fuel electrode: The fuel electrode embryo body is subjected to the fourth calcination to obtain the fuel electrode. The temperature of the fourth calcination is 1200-1300°C.
[0019] By adopting the above technical scheme, a fuel electrode with a gradient pore structure is prepared by a solid phase synthesis method, which is conducive to achieving precise control, the method is simple and efficient, and the applicability is wide. The fuel electrode pores obtained by the preparation method of the present invention are stacked pores, which effectively ensure the connectivity of the pores, and are more conducive to promoting the fuel gas transport inside the fuel electrode and improving its electrochemical performance. The structure of the stacked pores also promotes the cross-linking between nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO), increases the three-phase active sites, and greatly improves the rate of the electrochemical reaction. Among them, further, regulating the mass ratio and particle size of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) is conducive to promoting the regulation of pores and improving the connectivity between nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO). In addition, by controlling the first calcination temperature and the second calcination temperature, it is conducive to accurately controlling the growth kinetics of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO), thereby improving the accuracy of controlling the pore size and connectivity of the fuel electrode. The ball milling and the first calcination are combined to more accurately control the pores of the fuel electrode, and reduce the influence of the loss of raw material particle size during the preparation process on the control of pores. The preparation process of the fuel electrode preparation method of the present invention is simple and efficient, and is suitable for large-scale production.
[0020] According to another specific embodiment of the present invention, in the step of preparing the adhesion layer precursor, the particle size of gadolinium-doped ceria (CGO) is 300-500 nm.
[0021] According to another specific embodiment of the present invention, in the adhesion layer precursor preparation step, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.15-0.3; in the functional layer precursor preparation step, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.05-0.15; in the collector layer precursor preparation step, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.05-0.15.
[0022] According to another specific embodiment of the present invention, in the steps of preparing the adhesion layer precursor, the functional layer precursor and the current collecting layer precursor, the duration of the first calcination, the second calcination and the third calcination is 2 to 4 hours, the heating rate and the cooling rate of the first calcination, the second calcination and the third calcination are equal, and the heating rate and the cooling rate are 2 to 8°C / min.
[0023] According to another specific embodiment of the present invention, the fuel electrode embryo body preparation step further includes heating and drying after each coating, wherein the heating and drying temperature is 120-150° C., and the heating and drying time is 1-3 minutes.
[0024] According to another specific embodiment of the present invention, in the fuel electrode preparation step, the fourth calcination lasts for 2 to 4 hours, and the heating rate and cooling rate of the fourth calcination are equal, and the heating rate and cooling rate are 2 to 8°C / min.
[0025] According to another specific embodiment of the present invention, in the adhesion layer suspension slurry preparation step, the mass ratio of the adhesion layer precursor and the binder is 1 to 3:1; in the functional layer suspension slurry preparation step, the mass ratio of the functional layer precursor and the binder is 1 to 3:1; in the collector layer suspension slurry preparation step, the mass ratio of the collector layer precursor and the binder is 1 to 3:1.
[0026] According to another specific embodiment of the present invention, the binder is ethyl cellulose and diethylene glycol butyl ether acetate; in the adhesion layer suspension slurry preparation step, the ethyl cellulose accounts for 3 to 5 wt% of the binder mass; in the functional layer suspension slurry preparation and the collector layer suspension slurry preparation steps, the ethyl cellulose accounts for 2 to 4 wt% of the binder mass.
[0027] According to another specific embodiment of the present invention, in the steps of preparing the functional layer suspension slurry and the collector layer suspension slurry, the dispersant accounts for 1 to 1.5 wt % of the total mass of the functional layer precursor and the binder, and the dispersant accounts for 1 to 1.5 wt % of the total mass of the collector layer precursor and the binder.
[0028] According to another specific embodiment of the present invention, the dispersant is FA196.
[0029] According to another specific embodiment of the present invention, the thickness of the adhesion layer is 6-9 μm, the thickness of the functional layer is 15-20 μm, and the thickness of the collector layer is 10-15 μm.
[0030] According to another specific embodiment of the present invention, the pores formed in the fuel electrode are stacked pores.
[0031] According to another specific embodiment of the present invention, the porosity of the formed adhesion layer, functional layer and collector layer satisfies: the porosity of the adhesion layer is less than the porosity of the functional layer and less than the porosity of the collector layer. The porosity of the adhesion layer is 35% to 42%, the porosity of the functional layer is 46% to 50%, and the porosity of the collector layer is 53% to 60%.
[0032] In a second aspect, an embodiment of the present invention discloses a fuel electrode, which is coated on the surface of an electrolyte and includes, in order from the outside to the outside relative to the electrolyte, an adhesion layer, a functional layer, and a current collecting layer;
[0033] The adhesion layer is located between the electrolyte and the functional layer and includes gadolinium-doped ceria (CGO);
[0034] The functional layer includes nickel oxide (NiO) with a particle size of 1 to 2 μm and gadolinium-doped cerium oxide (CGO) with a particle size of 300 to 500 nm, and the mass ratio of nickel oxide (NiO) to gadolinium-doped cerium oxide (CGO) is 1 to 2:1;
[0035] The current collecting layer comprises nickel oxide (NiO) with a particle size of 4 to 5 μm and gadolinium-doped cerium oxide (CGO) with a particle size of 300 to 500 nm, and the mass ratio of nickel oxide (NiO) to gadolinium-doped cerium oxide (CGO) is 3 to 5:1; wherein the porosity of the adhesion layer, the functional layer and the current collecting layer satisfies:
[0036] The porosity of the adhesion layer is less than the porosity of the functional layer and less than the porosity of the current collecting layer.
[0037] By adopting the above technical scheme, the fuel electrode of the present invention has a three-layer gradient pore structure, which promotes the fuel electrode to have good ion transmission performance and electron transmission performance. The collector layer has a large porosity, which is conducive to reducing the ohmic resistance and the transmission of fuel gas, so that the fuel gas can be quickly transmitted to the functional layer, and the concentration polarization caused by the different partial pressures of the gas inside and outside the fuel electrode is reduced. The content of the electronic conductor nickel oxide (NiO) in the collector layer is controlled to be higher, which can not only improve the electronic conductivity but also improve the catalytic performance of the fuel gas. The functional layer, as the main area where the redox reaction occurs, has a smaller porosity that can effectively increase the specific surface area, thereby increasing the active sites of the electrochemical reaction. The adhesion layer is used to match the thermal expansion coefficient of the electrolyte, providing a stable mechanical structure for the overall structure. And by regulating the mass ratio of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO), the electrochemical reaction can be carried out stably and at a faster speed, which better promotes the transmission of electrons and ions. The mutual cooperation of the adhesion layer, the functional layer and the collector layer greatly improves the electrochemical reaction rate and stability of the fuel electrode.
[0038] According to another specific embodiment of the present invention, in the adhesion layer, the particle size of gadolinium-doped ceria (CGO) is 300-500 nm.
[0039] According to another specific embodiment of the present invention, in the adhesion layer, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.15-0.3; in the functional layer, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.05-0.15; in the collector layer, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.05-0.15.
[0040] According to another specific embodiment of the present invention, the thickness of the adhesion layer is 6-9 μm, the thickness of the functional layer is 15-20 μm, and the thickness of the collector layer is 10-15 μm.
[0041] According to another specific embodiment of the present invention, the pores of the fuel electrode are stacked pores.
[0042] In a third aspect, an embodiment of the present invention discloses a solid oxide fuel cell, including a fuel electrode obtained by the preparation method in any embodiment of the first aspect, or including a fuel electrode in any embodiment of the second aspect.
[0043] By adopting the above technical solution, a solid oxide fuel cell with good electrochemical performance and stability can be obtained.
[0044] In a fourth aspect, an embodiment of the present invention discloses a solid oxide fuel electrolysis cell, comprising a fuel pole obtained by the preparation method in any embodiment of the first aspect, or comprising a fuel pole in any embodiment of the second aspect.
[0045] By adopting the above technical scheme, a solid oxide fuel electrolyzer with good electrochemical performance and stability can be produced, which can be used to realize high-temperature electrolysis with an electrolyte-supported SOC as a core component, and serve as a core device for high-temperature electrolysis of water and carbon dioxide to produce hydrogen, carbon monoxide and other renewable fuels. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 It is a schematic diagram of the structure of the fuel electrode of the present invention;
[0047] Figure 2 Schematic diagram of the process of preparing the fuel electrode of Example 1 of the present invention;
[0048] Figure 3 This is a SEM image of the microstructure of the fuel electrode of Example 1 of the present invention;
[0049] Figure 4 This is a SEM image of the microstructure of the fuel electrode of Comparative Example 1 of the present invention;
[0050] Figure 5 It is a structural schematic diagram of the test bench of the present invention;
[0051] Figure 6 This is a test diagram of voltage-current-power density of the fuel electrode in SOFC mode in Example 1 of the present invention;
[0052] Figure 7 This is a test diagram of voltage-current-power density of the fuel electrode in Example 1 of the present invention under SOEC mode.
[0053] Explanation of symbols:
[0054] 1. Electrolyte, 2. Adhesion layer, 3. Functional layer, 4. Collector layer, 5. Ceramic fixture, 6. Collector wire, 7. High temperature resistant metal collector net, 8. Battery to be tested, 9. Sealing material, X. Outward direction relative to the electrolyte DETAILED DESCRIPTION
[0055] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may extend based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0056] It should be noted that in this specification, similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings.
[0057] To make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0058] The prior art mainly regulates the microstructure of the fuel electrode by using pore formers. Through careful research and exploration of the prior art, the inventors found that the electrochemical performance of the prior art pore former method for regulating the microstructure of nickel oxide / gadolinium doped cerium oxide (NiO / CGO) of the fuel electrode is not good. The working principle of the pore former in the prior art is that the pore former volatilizes into gas at a certain temperature, overflows from the material, and thus produces a porous structure in the material. The range of pore sizes regulated by the pore former is limited. Moreover, the process of pore former volatilization to form a porous structure will also greatly reduce the mechanical properties of the fuel electrode, thereby making the fuel electrode prone to fracture during operation. The inventors also found that in fact, the porous structure formed by the pore former is a structure similar to a porous sponge, in which the pores are isolated from each other, and the pore connectivity is low, which seriously restricts the mass transfer process and electrochemical reaction process of the fuel electrode. The inventors hope to improve the mass transfer and electrochemical reaction performance of the fuel electrode.
[0059] In the first aspect, the embodiments of the present invention propose for the first time a fuel electrode for nickel oxide / gadolinium doped cerium oxide (NiO / CGO) (reference Figure 1 ) is prepared by solid phase synthesis, comprising the following steps:
[0060] Preparation of adhesion layer precursor: Gadolinium-doped cerium oxide (CGO) is first calcined to obtain an adhesion layer precursor, and the temperature of the first calcination is 1000-1100° C.;
[0061] Preparation of adhesive layer suspension slurry: mixing an adhesive layer precursor and a binder to form an adhesive layer suspension slurry;
[0062] Preparation of functional layer precursor: After ball milling and mixing nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO), a second calcination is performed to obtain a functional layer precursor, wherein the particle size of the selected nickel oxide (NiO) is 1-2 μm, the particle size of the gadolinium-doped cerium oxide (CGO) is 300-500 nm, the mass ratio of nickel oxide (NiO) to gadolinium-doped cerium oxide (CGO) is 1-2:1 (that is, the mass ratio is between 1 and 2), and the temperature of the second calcination is 1000-1100° C.;
[0063] Functional layer suspension slurry preparation: functional layer precursor, binder and dispersant are mixed to form functional layer suspension slurry;
[0064] Preparation of a collector layer precursor: After ball milling and mixing nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO), the third calcination is performed to obtain a collector layer precursor, wherein the particle size of the selected nickel oxide (NiO) is 4-5 μm, the particle size of the gadolinium-doped cerium oxide (CGO) is 300-500 nm, the mass ratio of nickel oxide (NiO) to gadolinium-doped cerium oxide (CGO) is 3-5:1 (that is, the mass ratio is between 3 and 5), and the temperature of the third calcination is 1000-1100° C.;
[0065] Preparation of collector layer suspension slurry: mixing collector layer precursor, binder and dispersant to form collector layer suspension slurry;
[0066] Preparation of fuel electrode embryo: coating the adhesion layer suspension slurry, the functional layer suspension slurry and the collector layer suspension slurry on the surface of the electrolyte 1 in sequence to obtain a fuel electrode embryo with a three-layer structure of an adhesion layer 2, a functional layer 3 and a collector layer 4;
[0067] Preparation of fuel electrode: The fuel electrode embryo body is subjected to the fourth calcination to obtain the fuel electrode. The temperature of the fourth calcination is 1200-1300°C.
[0068] The present invention prepares a nickel oxide / gadolinium doped cerium oxide (NiO / CGO) fuel electrode with a gradient pore structure by a solid phase synthesis method, realizes precise control of parameters such as the particle size of the nickel oxide (NiO) and gadolinium doped cerium oxide (CGO) used, and then precisely controls the key parameters such as the porosity and pore size of the prepared fuel electrode, without the need to use a pore former. The method is simple, efficient, and has a wide range of applicability. However, although the solid phase synthesis method can avoid the use of a pore former, it is not certain how the specific solid phase synthesis method can obtain a suitable functional layer 3 and a current collecting layer 4 with porosity, whether the specific microstructure of the obtained fuel electrode can be maintained, and whether the fuel electrode prepared by the solid phase synthesis method can have excellent electrochemical performance. To this end, the inventors have determined the above technical scheme after various attempts and experiments, and proposed a preparation method for solid phase synthesis gradient pores specifically suitable for nickel oxide / gadolinium doped cerium oxide type fuel electrodes.
[0069] Specifically, the present invention first controls the first calcination temperature, the second calcination temperature, the third calcination temperature and the fourth calcination temperature of the adhesion layer 2, the functional layer 3 and the current collecting layer 4 during the solid phase synthesis process, and at the same time sets the mass ratio between the raw material powders nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) and the particle size of the raw material powders, which is beneficial to accurately control the growth kinetics of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) to obtain a nickel oxide / gadolinium-doped cerium oxide (NiO / CGO) fuel electrode with a porous structure.
[0070] Furthermore, the inventors found during the study that for the nickel oxide (NiO) / gadolinium doped cerium oxide (CGO) type fuel electrode, the characteristics of its electrochemical reaction are that nickel oxide (NiO) / gadolinium doped cerium oxide (CGO) is used as a catalyst, and the chemical reaction occurs at the position where the three phases of nickel oxide (NiO), gadolinium doped cerium oxide (CGO) and fuel gas exist at the same time. This position can be called a three-phase active site. The presence of the three-phase active site increases the catalytic activity and the rate of the electrochemical reaction, thereby improving the electrical performance of the fuel electrode. The pores formed in the fuel electrode obtained by the preparation method of the present invention by controlling the solid phase synthesis and the particle size of the synthetic raw material powder are stacked pores, which refer to the gaps between particles due to the accumulation of particles. The stacked pores can increase the connectivity of the pores, which is more conducive to promoting the transportation of fuel gas inside the fuel electrode, thereby improving its electrochemical performance. The inventors also found that through the solid phase synthesis method of the present invention, and the specific preparation method in the solid phase synthesis is specially designed, the catalytic activity of the nickel oxide-gadolinium doped cerium oxide-fuel gas system can be improved. The reason is that, on the one hand, the specific improvement of the preparation method of the present invention forms a stacked pore with a specific stacking state and a specific pore structure, which is particularly suitable for nickel oxide (NiO) / gadolinium-doped cerium oxide (CGO) fuel electrodes, and the obtained special stacked pore structure is beneficial to catalytic activity. On the other hand, in the fuel electrode prepared by the present invention, nickel oxide (NiO) is used to transport electrons, and gadolinium-doped cerium oxide (CGO) is used to transport ions. The structure of the stacked pores promotes the cross-linking between nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO), thereby increasing the three-phase active sites of nickel oxide-gadolinium-doped cerium oxide-fuel gas.
[0071] Obtaining a fuel electrode structure with a stable structure and capable of ensuring excellent electrochemical performance is the result of comprehensive settings of the following parameters, and the ranges of the parameter settings are specifically as described above. The mass ratio of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) in the functional layer 3 and the particle sizes of nickel oxide and gadolinium-doped cerium oxide are set, the mass ratio of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) in the collector layer 4 and the particle sizes of nickel oxide and gadolinium-doped cerium oxide are set, and the calcination temperatures at different stages are coordinated to obtain stacked pores with a specific pore structure, and the obtained fuel electrode satisfies the gradient pore structure of the porosity of the adhesion layer 2 < the porosity of the functional layer 3 < the porosity of the collector layer 4, and the larger porosity of the collector layer 4 is conducive to reducing the ohmic current. The functional layer 3 is used as the main area for the redox reaction. By setting a smaller porosity than the collector layer 4, the fuel gas transmitted from the collector layer 4 can fully react with the functional layer 3. In addition, the improvement of the above preparation method forms a stacked pore structure suitable for the functional layer 3. Such stacked pores can have more three-phase active sites, thereby improving the catalytic activity of the functional layer 3 and promoting the catalytic reaction. The adhesion layer 2 has the smallest porosity and is more compatible with the thermal expansion coefficient of the electrolyte 1, which can greatly improve the mechanical stability of the battery. In addition, by controlling the first calcination temperature, the second calcination temperature and the third calcination temperature at 1000-1100°C, calcination is first performed, which is beneficial to the formation of a stable interface between each layer of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) in the fuel electrode and prevents excessive growth, leaving space for the fourth calcination to control continued growth; then the fourth calcination is performed at a temperature of 1200-1300°C, and combined with the above steps, the three-layer structure of the adhesion layer, the functional layer and the current collecting layer is sintered into a whole, which is closer to each other and promotes the connectivity between the stacked pores; thereby improving the accuracy of controlling the pore size and connectivity of the fuel electrode.
[0072] Furthermore, in the process of preparing the functional layer precursor and the current collecting layer precursor, the pores of the fuel electrode are precisely controlled by combining ball milling and the second calcination, as well as the ball milling and the third calcination. Specifically, the second calcination or the third calcination promotes the growth of the particle size of the raw nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO), thereby reducing the particle size loss of the raw nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) during ball milling.
[0073] Therefore, the present invention is a fuel electrode with a gradient pore structure obtained by the above technical solution. Specifically, the preparation method of the fuel electrode of the present invention obtains a fuel electrode with good mass transfer and electrical properties through solid phase synthesis, setting the mass ratio between raw material powders and the particle size of the raw material powders, calcination temperatures at different stages and ball milling. The preparation process is simple and efficient, and is suitable for large-scale production.
[0074] The gadolinium-doped cerium oxide (CGO) is a composite oxide material in which the gadolinium (Gd) element is doped into the lattice structure of cerium oxide (CeO2), and the chemical formula is usually expressed as Ce 1-x G x O2, where x represents the molar ratio of gadolinium doping in cerium oxide, 0<x<1. Gadolinium doping can increase the conductivity of cerium oxide. After doping, gadolinium-doped cerium oxide (CGO) maintains the excellent redox properties of cerium oxide and has good chemical and structural stability at high temperatures.
[0075] Furthermore, in the above embodiment, the gadolinium-doped cerium oxide (CGO) particles used in the functional layer 3 and the collector layer 4 are of equal size, which is beneficial to simplify the process control parameters and facilitate better regulation of the porosity of the functional layer 3 and the collector layer 4 .
[0076] In the above embodiment, ball milling is limited before the second calcination in the preparation step of the functional layer precursor, and ball milling is limited before the third calcination in the preparation step of the collector layer precursor. For example, the ball milling speed is 150-200 rpm, and the ball milling time is 4-8 hours, so as to better cooperate with the second calcination or the third calcination, and accurately control the growth kinetics of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO).
[0077] The adhesion layer can be made into a layer with a high density, so as to play the role of isolating the functional layer 3 and the electrolyte 1, as well as the fuel gas. In another embodiment of the present invention, in the preparation step of the adhesion layer precursor, gadolinium-doped cerium oxide (CGO) with a particle size of 300-500nm is selected, and after the first calcination at 1000-1100°C and the fourth calcination at 1200-1300°C, it can have a smaller porosity, which can not only prevent the functional layer 3 from contacting the electrolyte 1 and prevent the fuel gas from reaching the electrolyte 1, but also help to reduce the mass transfer resistance, promote ion transfer to the electrolyte, and increase the catalytic reaction rate. Furthermore, in the preparation step of the adhesion layer precursor, the selected gadolinium-doped cerium oxide of 300-500nm can be ball-milled, the ball milling speed is 150-200rpm, the ball milling time is 4-8h, and then the first calcination is performed.
[0078] In the preparation step of the adhesion layer precursor of the present invention, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.15-0.3; in the preparation step of the functional layer precursor, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.05-0.15; in the preparation step of the collector layer precursor, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.05-0.15. The inventors found that the stability of the fuel electrode structure is conducive to improving the electrochemical cycle stability of the fuel electrode. Among them, adjusting the difference in thermal expansion coefficients between the adhesion layer 2 and the electrolyte 1 so that the matching of the thermal expansion coefficients of the adhesion layer 2 and the electrolyte 1 can improve the stability of the fuel electrode, thereby reducing the thermal stress generated during the sintering process and enhancing the bonding strength between the electrolyte 1 and the adhesion layer 2. Therefore, the possibility of peeling between the adhesion layer 2 and the electrolyte 1 is reduced, the ion transport resistance of the fuel electrode is reduced, and the electrochemical performance is improved. Based on this, the inventors have found that when the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) in the adhesion layer 2 is set to the above range, its thermal expansion coefficient is close to the expansion coefficient of the electrolyte 1, which can greatly improve the mechanical stability of the solid oxide fuel cell or solid oxide fuel electrolysis cell. In addition, setting the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) in the adhesion layer 2 to 0.15-0.3 is also conducive to the improvement of the ability to transport ions and carry electrons, and is convenient for transmission to the counter electrode side of the fuel electrode through the electrolyte 1. Preferably, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) in the adhesion layer 2 can be 0.2-0.25. Furthermore, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) in the functional layer 3 is 0.05-0.15, which can match the thermal expansion coefficients of the gadolinium-doped cerium oxide (CGO) and nickel oxide (NiO), avoid the separation of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) at the same temperature due to the difference in mechanical properties, and is conducive to the combination of the two. And the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) in the collector layer 4 is 0.05-0.15, which can also match the thermal expansion coefficients of the gadolinium-doped cerium oxide (CGO) and nickel oxide (NiO) in the collector layer 4. Finally, by setting the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) of the adhesion layer 2, the functional layer 3 and the collector layer 4 within the above range, the stability of the fuel electrode is improved as a whole, thereby improving the electrochemical cycle stability of the fuel electrode. In addition, the above-mentioned doping amount refers to the molar ratio of the gadolinium (Gd) element in the cerium oxide (CeO2) lattice.
[0079] Furthermore, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) of the collector layer 4 is equal to the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) of the functional layer 3, so that the expansion coefficients of the collector layer 4 and the functional layer 3 are matched, which is more conducive to the stability of the fuel electrode structure.
[0080] In the steps of preparing the adhesion layer precursor, the functional layer precursor and the collector layer precursor, the first calcination has a calcination time of 2-4 hours, a heating rate of 2-8°C / min, a cooling rate of 2-8°C / min, and the heating rate and the cooling rate are equal; the second calcination has a calcination time of 2-4 hours, a heating rate of 2-8°C / min, a cooling rate of 2-8°C / min, and the heating rate and the cooling rate are equal; the third calcination has a calcination time of 2-4 hours, a heating rate of 2-8°C / min, a cooling rate of 2-8°C / min, and the heating rate and the cooling rate are equal. The combination of the above conditions is conducive to better control of the growth dynamics of the precursor preparation.
[0081] The fuel electrode embryo preparation step also includes heating and drying after each coating, the heating and drying temperature is 120-150°C, and the heating and drying time is 1-3 minutes. The above conditions are used to make each layer of the three-layer fuel electrode embryo a stable structure. For example, after the adhesion layer suspension slurry is coated on the electrolyte surface, a solid adhesion layer 2 is formed by the above drying, and the functional layer suspension slurry is continuously coated on the solid adhesion layer surface, and a solid functional layer 3 is formed by the above drying, and the current collection layer suspension slurry is continuously coated on the solid functional layer surface, and a solid current collection layer 4 is formed by the above drying, so as to obtain a fuel electrode embryo having a three-layer structure of adhesion layer 2, functional layer 3 and current collection layer 4.
[0082] In the fuel electrode preparation step, the fourth calcination lasts for 2 to 4 hours, and the heating rate and cooling rate of the fourth calcination are equal, and the heating rate and cooling rate are 2 to 8°C / min. The above conditions are combined to better control the growth dynamics of the raw material powder during the fourth calcination preparation process.
[0083] In the preparation step of the adhesion layer suspension slurry, the mass ratio of the adhesion layer precursor and the binder is 1 to 3:1 (that is, the mass ratio is between 1 and 3); in the preparation step of the functional layer suspension slurry, the mass ratio of the functional layer precursor and the binder is 1 to 3:1 (that is, the mass ratio is between 1 and 3); in the preparation step of the collector layer suspension slurry, the mass ratio of the collector layer precursor and the binder is 1 to 3:1 (that is, the mass ratio is between 1 and 3). By adjusting the content of the binder, it is helpful to better prepare the film of each layer structure of the adhesion layer 2, the functional layer 3 and the collector layer 4, and enhance the connectivity of the pore structure. Combined with the aforementioned preparation method, a more stable and uniform fuel electrode is obtained.
[0084] Furthermore, the binder is ethyl cellulose and diethylene glycol butyl ether acetate; in the step of preparing the adhesive layer suspension slurry, ethyl cellulose accounts for 3-5wt% of the binder mass; in the step of preparing the functional layer suspension slurry and the collector layer suspension slurry, ethyl cellulose accounts for 2-4wt% of the binder mass. By using the solution of ethyl cellulose and diethylene glycol butyl ether acetate as a binder, it is beneficial to the bonding and cross-linking of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO), and the film-forming ability is good. Since the adhesion layer 2 only contains gadolinium-doped cerium oxide (CGO) with a particle size of 300-500nm, in order to avoid the agglomeration of nano-particles and affect the pore structure, the mass content of ethyl cellulose in the binder in the step of preparing the adhesive layer suspension slurry is higher than that of the other two layers. The high mass content of ethyl cellulose means that the viscosity of the binder is high. By optimizing the mixing ratio of the binder and the precursor and optimizing the binder composition, the connectivity of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) is ensured, thereby further improving the performance of the fuel electrode of the present invention, so that the prepared fuel electrode has good electronic conductivity and ionic conductivity at the same time.
[0085] In the steps of preparing the functional layer suspension slurry and the collector layer suspension slurry, the dispersant accounts for 1 to 1.5 wt% of the total mass of the functional layer precursor and the binder, and the dispersant accounts for 1 to 1.5 wt% of the total mass of the collector layer precursor and the binder. The dispersant is set to the above range, which can avoid the dispersion unevenness caused by the large particle size difference between nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) in the functional layer and the collector layer, and is conducive to promoting the cross-linking of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) in the fuel pole and increasing the connectivity of its structure, thereby increasing more active sites, and is more conducive to maintaining a certain viscosity of each layer of slurry, which is conducive to film formation. Further, the dispersant is FA196, which further improves the cross-linking and dispersion uniformity of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO).
[0086] In any of the above embodiments, the thickness of the adhesion layer 2 is 6-9 μm, the thickness of the functional layer 3 is 15-20 μm, and the thickness of the collector layer 4 is 10-15 μm. The pores of the fuel electrode are stacked pores. Specifically, the pores formed by solid phase synthesis in the functional layer and the collector layer are stacked pores. Further, the adhesion layer formed by calcining 300-500 nm of gadolinium-doped cerium oxide (CGO) also has stacked pores. Among them, the porosity of the adhesion layer 2, the functional layer 3 and the collector layer 4 satisfies: the porosity of the adhesion layer 2 < the porosity of the functional layer 3 < the porosity of the collector layer 4, the porosity of the adhesion layer 2 is 35%-42%, the porosity of the functional layer 3 is 46%-50%, and the porosity of the collector layer 4 is 53%-60%. Combined with the mutual cooperation of the above-mentioned features, the fuel electrode of the present invention has good mass transfer and electrochemical reaction performance.
[0087] Second, continue to refer to Figure 1 The embodiment of the present invention discloses a fuel electrode, which is coated on the surface of the electrolyte and includes, in order from the electrolyte to the outside, an adhesion layer 2, a functional layer 3 and a current collecting layer 4, and in order from the electrolyte to the outside, for example Figure 1 The X direction in
[0088] The adhesion layer 2 is located between the electrolyte 1 and the functional layer 3;
[0089] The adhesion layer 2 includes gadolinium-doped ceria (CGO);
[0090] The functional layer 3 includes nickel oxide (NiO) with a particle size of 1 to 2 μm and gadolinium-doped cerium oxide (CGO) with a particle size of 300 to 500 nm, and the mass ratio of nickel oxide (NiO) to gadolinium-doped cerium oxide (CGO) is 1 to 2:1 (that is, the mass ratio is between 1 and 2);
[0091] The collector layer 4 includes nickel oxide (NiO) with a particle size of 4 to 5 μm and gadolinium-doped cerium oxide (CGO) with a particle size of 300 to 500 nm, and the mass ratio of nickel oxide (NiO) to gadolinium-doped cerium oxide (CGO) is 3 to 5:1 (that is, the mass ratio is between 3 and 5);
[0092] The porosity of the adhesive layer 2 is less than the porosity of the functional layer 3 and less than the porosity of the current collecting layer 4 .
[0093] By adopting the above technical scheme, the fuel electrode of the present invention has a three-layer gradient pore structure, which promotes the fuel electrode to have good ion transmission performance and electron transmission performance. Among them, the adhesion layer 2 is used to match the thermal expansion coefficient of the electrolyte 1 and has catalytic activity; the functional layer 3 is used as the main area for the redox reaction; the collector layer 4 is used to transmit electrons and transport fuel gas and has catalytic activity. The collector layer 4 has a large porosity, which is conducive to reducing the ohmic resistance and the transmission of the fuel gas, so that the fuel gas can be quickly transmitted to the functional layer 3, and the concentration polarization caused by the different partial pressures of the gas inside and outside the fuel electrode is reduced. Controlling the content of the electronic conductor nickel oxide (NiO) in the collector layer 4 to be higher can not only improve the electronic conductivity but also improve the catalytic performance of the fuel gas. As the main area for the redox reaction, the smaller porosity of the functional layer 3 can effectively increase the specific surface area, thereby increasing the active sites of the electrochemical reaction. The adhesion layer 2 is used to match the thermal expansion coefficient of the electrolyte 1, providing a stable mechanical structure for the overall structure. And by adjusting the mass ratio of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO), the electrochemical reaction can be carried out stably and at a faster speed, which better promotes the transmission of electrons and ions. The mutual cooperation of the adhesion layer 2, the functional layer 3 and the current collecting layer 4 greatly improves the electrochemical reaction rate and stability of the fuel electrode.
[0094] In the adhesion layer 2, the particle size of gadolinium-doped cerium oxide (CGO) is 300-500 nm. As a result, the adhesion layer 2 can have a smaller porosity, which is beneficial to reducing the mass transfer resistance, and makes the fuel electrode of the present invention have an excellent three-layer gradient pore structure, which is more conducive to the transportation of fuel gas and higher catalytic activity, and cooperates with any of the above-mentioned embodiments to further improve the electrochemical performance of the fuel electrode of the present invention.
[0095] Furthermore, in the adhesion layer 2, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.15-0.3; in the functional layer 3, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.05-0.15; in the collector layer 4, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.05-0.15. By controlling the doping amount of gadolinium in each layer of gadolinium-doped cerium oxide (CGO), the thermal expansion coefficients of the four-layer structure of the electrolyte 1, the adhesion layer 2, the functional layer 3 and the collector layer 4 are matched with each other, thereby forming a fuel electrode with a stable structure and strong mass transfer ability. Among them, the thickness of the adhesion layer 2 is 6-9μm, the thickness of the functional layer 3 is 15-20μm, and the thickness of the collector layer 4 is 10-15μm. The adhesion layer 2 is set to the above thickness to reduce the ion transmission resistance while ensuring sufficient mechanical strength to match the electrolyte 1; the functional layer 3 is set to the above thickness to ensure a high specific surface area, thereby ensuring more active sites, ensuring high catalytic activity, and reducing resistance; the collector layer 4 is set to the above thickness to facilitate the collection of electrons and promote electron transmission.
[0096] In any of the above embodiments, the pores of the fuel electrode are stacked pores. The stacked pore structure promotes the cross-linking between nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) and the connectivity of the pores, which is beneficial to the diffusion and mass transfer of the reaction gas in the fuel electrode, and increases the three-phase active sites where nickel oxide (NiO), gadolinium-doped cerium oxide (CGO) and fuel gas contact. The presence of the three-phase active sites greatly improves its catalytic activity.
[0097] In a third aspect, an embodiment of the present invention discloses a solid oxide fuel cell, including a fuel electrode obtained by the preparation method in any embodiment of the first aspect, or including a fuel electrode in any embodiment of the second aspect.
[0098] By adopting the above technical solution, a solid oxide fuel cell with good electrochemical performance and stability can be obtained.
[0099] In a fourth aspect, an embodiment of the present invention discloses a solid oxide fuel electrolysis cell, comprising a fuel pole obtained by the preparation method in any embodiment of the first aspect, or comprising a fuel pole in any embodiment of the second aspect.
[0100] By adopting the above technical scheme, a solid oxide fuel electrolyzer with good electrochemical performance and stability can be produced, which can be used to realize high-temperature electrolysis with an electrolyte-supported SOC as a core component, and serve as a core device for high-temperature electrolysis of water and carbon dioxide to produce hydrogen, carbon monoxide and other renewable fuels.
[0101] Example 1
[0102] The schematic diagram of the process for preparing the fuel electrode in Example 1 is as follows Figure 2 As shown, the specific steps include:
[0103] Preparation of adhesion layer precursor: Weigh 10g of gadolinium-doped cerium oxide (CGO) with a particle size of 400nm and a gadolinium doping amount of 0.2, that is, CG 0.2 O. CG 0.2 O was placed in a reactor for the first calcination, and the temperature was increased from room temperature to the first calcination temperature of 1100°C at a heating rate of 3°C / min under an air atmosphere for 2 hours, and then cooled to room temperature at a cooling rate of 3°C / min to obtain an adhesion layer precursor.
[0104] Preparation of adhesion layer suspension slurry: weigh 5 g of adhesion layer precursor, add 2.5 g of binder containing 4 wt% ethyl cellulose, mix thoroughly to obtain adhesion layer suspension slurry; wherein the binder is ethyl cellulose and diethylene glycol butyl ether acetate, and the mass ratio of the adhesion layer precursor to the binder is 2:1.
[0105] Preparation of functional layer precursor: Weigh 6g of NiO with a particle size of 1-2μm, weigh 4g of gadolinium-doped cerium oxide (CGO) with a particle size of 400nm and a gadolinium doping amount of 0.1, that is, CG 0.1 O, NiO and CG 0.1 O was placed in an agate ball milling jar and ball-milled in a planetary ball mill at a rotation speed of 180 rpm for 6 hours. The mixture was then placed in a ceramic reactor and heated from room temperature to a second calcination temperature of 1100°C at a heating rate of 3°C / min in an air atmosphere and calcined for 2 hours. The temperature was then cooled to room temperature at a cooling rate of 3°C / min to obtain a functional layer precursor. The mass ratio of nickel oxide (NiO) to gadolinium-doped cerium oxide (CGO) was 1.5:1.
[0106] Preparation of functional layer suspension slurry: weigh 5g of functional layer precursor, add 2.5g of binder containing 3wt% ethyl cellulose and 0.0375g of dispersant, mix thoroughly to obtain functional layer suspension slurry; wherein the binder is ethyl cellulose and diethylene glycol butyl ether acetate, the mass ratio of the functional layer precursor to the binder is 2:1, the dispersant is FA196, and the dispersant accounts for 0.5wt% of the total mass of the functional layer precursor and the binder.
[0107] Preparation of collector layer precursor: Weigh 8g of NiO with a particle size of 4-5μm, weigh 2g of gadolinium-doped cerium oxide (CGO) with a particle size of 400nm and a gadolinium doping amount of 0.1, that is, CG 0.1 O, NiO and CG 0.1 O powder is placed in an agate ball mill, ball-milled and mixed in a planetary ball mill at a speed of 180 rpm for 6 hours, and then the mixture is placed in a ceramic reactor, and the temperature is increased from room temperature to a third calcination temperature of 1100°C at a heating rate of 3°C / min in an air atmosphere and calcined for 2 hours, and then cooled to room temperature at a cooling rate of 3°C / min to obtain the collector layer precursor; wherein the mass ratio of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) is 4:1.
[0108] Preparation of collector layer suspension slurry: weigh 5 g of the collector layer precursor, add 2.5 g of a binder containing 3 wt% ethyl cellulose and 0.0375 g of a dispersant, mix thoroughly, and obtain a collector layer suspension slurry; wherein the binder is ethyl cellulose and diethylene glycol butyl ether acetate, the mass ratio of the collector layer precursor to the binder is 2:1, the dispersant is FA196, and the dispersant accounts for 0.5 wt% of the total mass of the collector layer precursor and the binder.
[0109] Preparation of fuel electrode embryo: Take the adhesion layer suspension slurry, the functional layer suspension slurry and the collector layer suspension slurry, and use a screen printing machine to sequentially coat them on a 3YSZ electrolyte with an area of 60mm×60mm and a thickness of 90±10μm; the thickness of the adhesion layer is 6~9μm, the thickness of the functional layer is 15~20μm, and the thickness of the collector layer is 10~15μm.
[0110] Preparation of fuel electrode: After drying the fuel electrode embryo, transfer it to a muffle furnace and heat it from room temperature to the fourth calcination temperature of 1300°C at a heating rate of 3°C / min in an air atmosphere for 2 hours. Then, cool it to room temperature at a cooling rate of 3°C / min to obtain the fuel electrode. The SEM image of the microstructure of the fuel electrode is shown in the figure. Figure 3 shown.
[0111] In the fuel electrode of Example 1 of the present invention, the porosity of the adhesion layer 2 is 41.52%, the porosity of the functional layer 3 is 49.85%, and the porosity of the current collecting layer 4 is 53.36%.
[0112] Depend on Figure 3 It can be seen that the fuel electrode of the present invention has a gradient pore structure, the porosity of the adhesion layer 2 is less than the porosity of the functional layer 3 and less than the porosity of the collector layer 4, and the pores of the fuel electrode of the present invention are stacked pores.
[0113] Comparative Example 1
[0114] The preparation method of the fuel electrode of Comparative Example 1 specifically includes the following steps:
[0115] Preparation of adhesion layer suspension slurry: Weigh 5 g of gadolinium-doped cerium oxide (CGO) with a particle size of 400 nm and a gadolinium doping amount of 0.2, that is, CG 0.2 O, add 4g of a binder containing 4wt% ethyl cellulose, mix thoroughly, and obtain an adhesion layer suspension slurry; wherein the binder is ethyl cellulose and diethylene glycol butyl ether acetate, and the mass ratio of the adhesion layer precursor to the binder is 1.25:1.
[0116] Preparation of functional layer precursor: Weigh 6g of NiO with a particle size of 1-2μm, weigh 4g of gadolinium-doped cerium oxide (CGO) with a particle size of 400nm and a gadolinium doping amount of 0.1, that is, CG 0.1 O, NiO and CG 0.1 O was placed in an agate ball mill jar and ball-milled in a planetary ball mill at a rotation speed of 300 rpm for 24 hours to obtain a functional layer precursor; wherein the mass ratio of nickel oxide (NiO) to gadolinium-doped cerium oxide (CGO) was 1.5:1.
[0117] Preparation of functional layer suspension slurry: weigh 5g of functional layer precursor, add 3.25g of binder containing 4wt% ethyl cellulose, 0.25g of pore-forming agent with an average particle size of 5μm and 0.0425g of dispersant, mix well to obtain functional layer suspension slurry; wherein the binder is ethyl cellulose and diethylene glycol butyl ether acetate, the mass ratio of the functional layer precursor to the binder is 1:0.65, the pore-forming agent is polymethyl methacrylate (PMMA) powder, and the mass ratio of the pore-forming agent to the functional layer precursor is 20:1; the dispersant is FA196, and the dispersant accounts for 0.5wt% of the total mass of the functional layer precursor, the pore-forming agent and the binder.
[0118] Preparation of collector layer precursor: Weigh 8g of NiO with a particle size of 4-5μm, weigh 2g of gadolinium-doped cerium oxide (CGO) with a particle size of 400nm and a gadolinium doping amount of 0.1, that is, CG 0.1 O, NiO and CG 0.1 O was placed in an agate ball mill jar and ball-milled in a planetary ball mill at a rotation speed of 300 rpm for 24 hours to obtain a collector layer precursor; wherein the mass ratio of nickel oxide (NiO) to gadolinium-doped cerium oxide (CGO) was 4:1.
[0119] Preparation of collector layer suspension slurry: weigh 5g of collector layer precursor, add 3.25g of binder containing 4wt% ethyl cellulose, 0.25g of pore-forming agent with an average particle size of 5μm and 0.0425g of dispersant, mix thoroughly to obtain collector layer suspension slurry; wherein the binder is ethyl cellulose and diethylene glycol butyl ether acetate, the mass ratio of the collector layer precursor to the binder is 1:0.65, the pore-forming agent is polymethyl methacrylate (PMMA) powder, and the mass ratio of the pore-forming agent to the collector layer precursor is 20:1; the dispersant is FA196, and the dispersant accounts for 0.5wt% of the total mass of the collector layer precursor, the pore-forming agent and the binder.
[0120] Preparation of fuel electrode embryo: Take the adhesion layer suspension slurry, the functional layer suspension slurry and the collector layer suspension slurry, and use a screen printing machine to sequentially coat them on a 3YSZ electrolyte with an area of 60mm×60mm and a thickness of 90±10μm; after drying the fuel electrode embryo, transfer it to a muffle furnace, and heat it from room temperature to the fourth calcination temperature of 1300℃ in an air atmosphere at a heating rate of 3℃ / min. The calcination time is 2h, and then the temperature is cooled to room temperature at a cooling rate of 3℃ / min to obtain the fuel electrode. The SEM image of the microstructure of the fuel electrode of Comparative Example 1 is shown in FIG. Figure 4 shown.
[0121] In the preparation process of Comparative Example 1, although the mass ratio between the raw material powders and the particle size of the raw material powders are set to be the same as those of the present invention, Figure 4 It can be seen that the powders in the fuel electrode of Comparative Example 1 are bonded together as a whole, and no pores are formed as in the fuel electrode of the present invention. Figure 4 It can also be seen that the pores prepared by the PMMA pore-forming agent method in Comparative Example 1 are isolated from each other and are pores formed by the pore-forming agent itself volatilizing under heat.
[0122] To facilitate the understanding of the present invention, the voltage-current-power density test method of the fuel electrode in SOFC and SOEC modes is described:
[0123] The performance of Example 1 in SOFC and SOEC modes was tested on a test bench using a four-wire method such as Figure 5 As shown, the high temperature metal current collector net 7 on both sides of the fuel electrode and the air electrode of the battery 8 to be tested is fixed by a ceramic fixture 5, and a sealing material 9 is placed between the battery 8 to be tested and the ceramic fixture 5 to allow hydrogen and air to be introduced into the fuel electrode and the air electrode respectively. The current collector wire 6 is led outward from the high temperature metal current collector net 7 and connected to the electrochemical workstation, electronic load and other measuring instruments to measure the battery performance. The air electrode is a LSC / CGO composite air electrode, and the fuel electrode and the air electrode are printed on both sides of the electrolyte in the battery 8 to be tested. The test results are shown in FIG. Figure 6-7 shown.
[0124] like Figure 6 The test diagram of the fuel electrode in the SOFC mode of Example 1 is shown. Figure 4 It can be seen that the maximum output power density of the fuel electrode in Example 1 of the present invention is 0.445 W / cm 2 , which is about the maximum output power density of comparative example 1, 0.223 W / cm 2 The absolute value of the slope of the voltage-current density curve in the figure corresponds to the surface resistance of the fuel electrode. The surface resistance of the fuel electrode in Example 1 of the present invention is 0.783Ω·cm 2 , which is about the surface resistance of Comparative Example 1, 1.480Ω·cm 2 50% of.
[0125] like Figure 7 The test diagram of the fuel electrode in Example 1 under the SOEC mode is shown by Figure 7 It can be seen that the absolute value of the slope of the voltage-current density curve in the figure corresponds to the surface resistance of the fuel electrode. The surface resistance of the fuel electrode in Example 1 of the present invention is 1.209Ω·cm 2 , which is lower than the surface resistance of Comparative Example 1 (1.431Ω·cm) 2Since the greater the power density of the fuel electrode, the smaller the surface resistance, it can be seen that the electrochemical performance of the battery using the fuel electrode of Example 1 of the present invention is better.
[0126] In summary, the present invention prepares a fuel electrode with a gradient pore structure by solid phase synthesis method for nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) powders, and the raw materials are easily available and widely sourced. And by ball milling and calcination methods, the particle size and other parameters of the powder material are controlled, and the raw material powders from different sources are highly adaptable. Then, by controlling the particle size of the powder, the key parameters such as the porosity and pore size of the prepared fuel electrode are directly controlled, without the need to use a pore-forming agent, which is simpler and more efficient. The pores of the fuel electrode prepared in this way are stacked pores, which effectively ensure the connectivity of the pores and are more conducive to gas transport inside the fuel electrode. And the fuel electrode of the present invention has a gradient pore structure, and the prepared fuel electrode uses powders of different particle sizes in different structural layers. Stepped pores can be obtained by reasonable preparation parameter regulation, which is more conducive to mass transfer and electrochemical reactions in the fuel electrode. By optimizing the binder composition and the mixing ratio of the binder to the precursor, the connectivity of nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO) is ensured, so that the prepared fuel electrode has good electronic conductivity and ion conductivity. In addition, the fuel electrode of the present invention can be used to realize high-temperature electrolysis with an electrolyte-supported SOC as the core component, as a core device for high-temperature electrolysis of water and carbon dioxide to produce hydrogen, carbon monoxide and other renewable fuels.
[0127] Although the present invention has been illustrated and described with reference to certain preferred embodiments of the present invention, it should be understood by those skilled in the art that the above is a further detailed description of the present invention in conjunction with specific embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Those skilled in the art may make various changes in form and details, including making several simple deductions or substitutions, without departing from the spirit and scope of the present invention.
Claims
1. A method for preparing a fuel electrode, characterized in that: The following steps are involved: Preparation of adhesion layer precursor: performing a first calcination on gadolinium-doped cerium oxide (CGO) to obtain the adhesion layer precursor, wherein the temperature of the first calcination is 1000-1100° C.; Preparation of adhesive layer suspension slurry: mixing the adhesive layer precursor and the binder to form an adhesive layer suspension slurry; Preparation of functional layer precursor: After ball milling and mixing nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO), a second calcination is performed to obtain the functional layer precursor, wherein the particle size of the nickel oxide (NiO) selected is 1-2 μm, the particle size of the gadolinium-doped cerium oxide (CGO) is 300-500 nm, the mass ratio of the nickel oxide (NiO) to the gadolinium-doped cerium oxide (CGO) is 1-2:1, and the temperature of the second calcination is 1000-1100° C.; Preparation of functional layer suspension slurry: mixing the functional layer precursor, the binder and the dispersant to form a functional layer suspension slurry; Preparation of the collector layer precursor: After ball milling and mixing nickel oxide (NiO) and gadolinium-doped cerium oxide (CGO), a third calcination is performed to obtain the collector layer precursor, wherein the particle size of the nickel oxide (NiO) selected is 4-5 μm, the particle size of the gadolinium-doped cerium oxide (CGO) is 300-500 nm, the mass ratio of the nickel oxide (NiO) to the gadolinium-doped cerium oxide (CGO) is 3-5:1, and the temperature of the third calcination is 1000-1100° C.; Preparation of collector layer suspension slurry: mixing the collector layer precursor, binder and dispersant to form collector layer suspension slurry; Preparation of fuel electrode embryo: applying the adhesion layer suspension slurry, the functional layer suspension slurry and the collector layer suspension slurry on the electrolyte surface in sequence to obtain a fuel electrode embryo with a three-layer structure of adhesion layer, functional layer and collector layer; Preparation of fuel electrode: The fuel electrode embryo is subjected to a fourth calcination to obtain the fuel electrode, and the temperature of the fourth calcination is 1200-1300°C.
2. The method for preparing a fuel electrode according to claim 1, characterized in that: In the adhesion layer precursor preparation step, the particle size of the gadolinium-doped cerium oxide (CGO) is 300-500 nm.
3. The method for preparing a fuel electrode according to claim 1, characterized in that: In the adhesion layer precursor preparation step, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.15-0.3; in the functional layer precursor preparation step, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.05-0.15; in the collector layer precursor preparation step, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.05-0.
15.
4. The method for preparing a fuel electrode according to claim 1, characterized in that: In the steps of preparing the adhesion layer precursor, the functional layer precursor and the current collecting layer precursor, the duration of the first calcination, the second calcination and the third calcination is 2 to 4 hours, the heating rate and cooling rate of the first calcination, the second calcination and the third calcination are equal, and the heating rate and cooling rate are 2 to 8°C / min.
5. The method for preparing a fuel electrode according to claim 1, characterized in that: The fuel electrode embryo preparation step also includes heating and drying after each coating, wherein the heating and drying temperature is 120 to 150° C. and the heating and drying time is 1 to 3 minutes.
6. The method for preparing a fuel electrode according to claim 1, characterized in that: In the fuel electrode preparation step, the duration of the fourth calcination is 2 to 4 hours, the heating rate and cooling rate of the fourth calcination are equal, and the heating rate and cooling rate are 2 to 8° C. / min.
7. The method for preparing a fuel electrode according to claim 1, characterized in that: In the step of preparing the adhesion layer suspension slurry, the mass ratio of the adhesion layer precursor to the binder is 1 to 3:1; in the step of preparing the functional layer suspension slurry, the mass ratio of the functional layer precursor to the binder is 1 to 3:1; in the step of preparing the collector layer suspension slurry, the mass ratio of the collector layer precursor to the binder is 1 to 3:
1.
8. The method for preparing a fuel electrode according to claim 7, characterized in that: The binder is ethyl cellulose and diethylene glycol butyl ether acetate; in the adhesion layer suspension slurry preparation step, the ethyl cellulose accounts for 3-5wt% of the binder mass; in the functional layer suspension slurry preparation step and the collector layer suspension slurry preparation step, the ethyl cellulose accounts for 2-4wt% of the binder mass.
9. The method for preparing a fuel electrode according to claim 1, characterized in that: In the steps of preparing the functional layer suspension slurry and the collector layer suspension slurry, the dispersant accounts for 1-1.5wt% of the total mass of the functional layer precursor and the binder, and the dispersant accounts for 1-1.5wt% of the total mass of the collector layer precursor and the binder.
10. The method for preparing a fuel electrode according to claim 9, characterized in that: The dispersant is FA196.
11. The method for preparing a fuel electrode according to claim 1, characterized in that: The thickness of the adhesive layer is 6-9 μm, the thickness of the functional layer is 15-20 μm, and the thickness of the current collecting layer is 10-15 μm.
12. The method for preparing a fuel electrode according to claim 1, characterized in that: The pores formed in the fuel electrode are accumulation pores.
13. The method for preparing a fuel electrode according to claim 2, characterized in that: The porosities of the formed adhesion layer, the functional layer and the collector layer satisfy: the porosity of the adhesion layer is less than the porosity of the functional layer and less than the porosity of the collector layer. The porosity of the adhesion layer is 35% to 42%, the porosity of the functional layer is 46% to 50%, and the porosity of the collector layer is 53% to 60%.
14. A fuel electrode, characterized in that: Coated on the surface of the electrolyte, relative to the electrolyte, outwardly, they are: an adhesion layer, a functional layer and a current collecting layer; The adhesion layer is located between the electrolyte and the functional layer and includes gadolinium-doped cerium oxide (CGO); The functional layer comprises nickel oxide (NiO) with a particle size of 1 to 2 μm and gadolinium-doped cerium oxide (CGO) with a particle size of 300 to 500 nm, and the mass ratio of the nickel oxide (NiO) to the gadolinium-doped cerium oxide (CGO) is 1 to 2:1; The current collecting layer comprises nickel oxide (NiO) with a particle size of 4 to 5 μm and gadolinium-doped cerium oxide (CGO) with a particle size of 300 to 500 nm, and the mass ratio of the nickel oxide (NiO) to the gadolinium-doped cerium oxide (CGO) is 3 to 5:1; wherein the porosity of the adhesion layer, the functional layer and the current collecting layer satisfies: The porosity of the adhesion layer is less than the porosity of the functional layer and less than the porosity of the current collecting layer.
15. The fuel electrode according to claim 14, characterized in that In the adhesion layer, the particle size of the gadolinium-doped cerium oxide (CGO) is 300-500 nm.
16. The fuel electrode according to claim 14, characterized in that In the adhesion layer, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.15-0.3; in the functional layer, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.05-0.15; in the collector layer, the doping amount of gadolinium in the gadolinium-doped cerium oxide (CGO) is 0.05-0.
15.
17. The fuel electrode according to claim 14, characterized in that The thickness of the adhesive layer is 6-9 μm, the thickness of the functional layer is 15-20 μm, and the thickness of the current collecting layer is 10-15 μm.
18. The fuel electrode according to any one of claims 14 to 17, characterized in that: The pores of the fuel electrode are stacked pores.
19. A solid oxide fuel cell, characterized in that: The fuel electrode comprises the fuel electrode obtained by the preparation method according to any one of claims 1 to 13, or the fuel electrode comprises the fuel electrode according to any one of claims 14 to 18.
20. A solid oxide fuel electrolysis cell, characterized in that: The fuel electrode comprises the fuel electrode obtained by the preparation method according to any one of claims 1 to 13, or the fuel electrode comprises the fuel electrode according to any one of claims 14 to 18.
Citation Information
Patent Citations
Solid oxide fuel cell anode, preparation method thereof, single cell and electric pile
CN115832327A
Method for preparing anode / electrolyte double-layer structure of solid oxide fuel cell by single grouting
CN101834296A
Gradient micro-porous configuration anode supporter slurry and preparation method thereof
CN109524687A
Reversible operation solid oxide fuel cell and preparation method thereof
CN116364989A
Ceria based solid electrolyte fuel cell and its manufacturing method
JP2006059611A
